The diversity of Pteridophytes in pepe watershed Surakarta polluted by household waste - Salsabila, Nadia; Ramadhani, Rina Wahyu; Mumpuni, Kistantia Elok (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2021)
Pepe River is one of the Bengawan Solo with a reasonably high level of water pollution due to the habit of the surroundings in throwing garbage into the river. Plants that can survive in polluted land conditions have a high tolerance level, called pioneer plants. One of them is ferns (Pteridophyta). This study aims to identify the type, abundance, Important Value Index (IVI), and index Diversity of pteridophytes plant diversity in the Pepe Watershed. The method used in this research is descriptive quantitative using the quadrat sampling technique method with a 1x1 meter plot. The sampling technique is using purposive sampling. Data analysis was conducted qualitatively and quantitatively. Analysis of diversity index data (H’) by Shannon-Wiener. Based on the results of the study found eight species of ferns from 5 families. There are Pteris vittata, Pteris biaurita L., Adiantum lunulatum Burm.fil., Adiantum latifolium Lam., Adiantum hispidulum Sw, Marsilea crenata C. Presl, Microlepia speluncae (L.) T. Moore, and Asplenium scandicinum Kaulf. Thisdiversity is included in the medium category with H'= 1.44. The fern with the highest abundance was Pteris vittata with 176 individuals, a density of 5.87 individuals/m2, a frequency of 0.53, and an IVI of 109.3%. Set side by set, the lowest abundance was Microlepia speluncae with eight individuals, a density of 0.27 individuals/m2, afrequency of 0.03, and IVI of 5.6%. Based on this, ferns can survive in polluted river areas. Information on the diversity of ferns found on critical land, especially rivers, is expected to provide initial information in overcoming other similar critical lands.